Role of Literature in Nation Building and Cultural Consciousness - Madhukar D. Hajare, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This paper explores the profound and multifaceted role of literature in the processes of nation-building and the cultivation of cultural consciousness. By examining historical and contemporary examples from diverse geopolitical contexts, this study argues that literature is not merely a reflection of a society, but an active agent in shaping its identity, values, and collective memory. The research analyzes how literary works, including epics, novels, poetry, and plays, have been used to create shared myths, historical narratives, and a sense of belonging among disparate communities. It investigates the ways in which literary figures have often served as national spokespersons and moral compasses, articulating aspirations and critiquing social ills. Furthermore, the paper delves into how literature preserves and transmits cultural traditions, languages, and unique worldviews, thereby fostering a distinct cultural consciousness. The conclusion highlights literature’s enduring capacity to not only unify a nation but also to challenge hegemonic narratives, ensuring a dynamic and self-critical national identity.
Keywords: Nation-building; Cultural Consciousness; Literature; Identity; Collective Memory